ANALISIS KELAYAKAN FINANSIAL USAHA BUDIDAYA PULLET (Studi Kasus pada UD Prapta di Desa Pasedahan, Kecamatan Manggis, Kabupaten Karangasem) - I M. G., Arta; Sukanata, I W.; Indrawati, R. R. (Jurnal Peternakan Tropika, 2016)
This study aims to determine financial feasibility of pullet production. The research was conducted from January to March 2016 at UD Prapta located in the Pasedahan village, Manggis District, Karangasem regency. Primary and secondary data were used in this study. The financial feasibility of this business was  analyzed based on the analysis of investment criteria, analysis Pay Back Period and Break Even Point. The results of this study indicate the financial feasibility that this business generates a positive NPV of Rp. 71.677.012, -, IRR of 19%, Net B / C of 1,33, Pay Back Period reached after 4,31 months and Break Even Point achived after the business run for 7,01 years. The results of the sensitivity analysis shows that this business reached breakeven when the number of production as many as 4.312 head, or at the pullet price of Rp. 45.104 - /pullet.
Keywords: pullet production, even point, financial feasibility